Technology structure of the US Live broiler production an empirical analysis using the non-homothetic translog cost function - Tan, Reynold D. (Iloilo City UP Visayas, 2009)
"The technology structure of the US live broiler production is explored using the annual Agri Stat, Inc. data, reports from the ERS/USDA, and the Bureau of Labor Statistics data from 1996-2003. Live broiler production inputs were feed, transportation, supervision, chicks, and grower services. Technology structures was analyzed using the homothetic translog cost function. The full static equilibrium cost function, input substitution, cross price elasticities of demand, and scale economies were calculated. Estimates were checked for theoretical consistency. Results showed that there exists substitutability among inputs for live broiler production. Generally, price statistics of conditional input demands were inelastic. Also, there is an evidence of minimal scale economies at 1.013. At the level of the mean, theoretical requisites were satisfied. Findings imply that instability and increasing factor input prices can be addressed by substitution. Moreover, efficiency gains can be derived by increasing the level of output capacity."
Keywords: Live broiler -- Farm produce; Cost structure